THE IMPACT OF RPA SOFTWARE TECHNOLOGY WORK PROCESSES ON THE QUALITY OF FINANCIAL REPORTS OF ACCOUNTANTS IN THE INDUSTRIAL ESTATES OF THAILAND - Isarankulanaayudhya, Kittiwat; Koomuang, Prawing; Thongruandee, Naphachakorn; Nakthuan , Wichuta (Journal of MCU Nakhondhat, 2025)
This research aims 1) To test the relationship and 2) To study the impact of the work process with RPA Software technology on the quality of financial reports of accountants in the industrial estates of Thailand. It is a quantitative research. The sample group is accountants in the industrial estates of Thailand, selected using a calculation formula, totaling 208 people. The research tools are questionnaires. Data collection is done with questionnaires. The statistics used in the research are percentage, mean, and standard deviation, multiple correlation analysis, and multiple regression analysis. The research results found that the impact of the RPA software technology process on the quality of financial reports of accountants in the industrial estates of Thailand in various aspects, including the suitability between work and technology, technology quality, user efficiency, and business results, has a positive relationship and impact on the overall quality of financial reports. Therefore, using RPA software in industrial estate accounting helps increase the quality of financial reports in terms of accuracy, timeliness, comparability, and auditability. The suitability between work and technology helps reduce errors, reduce manual workloads, and make the accounting process more standardized and in line with financial requirements. The quality and efficiency of RPA software helps accountants work faster, reduce redundant work, focus more on analyzing and planning financial strategies, reduce stress from repetitive work, and increase accountants’ job satisfaction. In addition, business results are improved by improving the automation of work processes, reducing operating costs, and increasing the speed of data processing. Organizations can use data to make strategic decisions more effectively.